Evaluación en paciente adulto mayor sexo masculino de 75 años de edad, con neumonía adquirida en la comunidad. - Calderón Rodríguez, Yamileth Alexandra (2020)
Community-acquired pneumonia, internally from infectious diseases, is a contentiously dangerous disease throughout the world, being more common in our surroundings, disturbing the community in both developed and developing countries alike. In the elderly, it is among the first causes of mortality with an infectious principle at a general level in the world, this is due to the fact that the mortality rate of this disease doubles as the age advances, presenting significant morbidity. Carrying out this work is feasible, since it will help us to gather relevant information about the incidence of this condition in older adults, and thus generate a point of reference for future studies of this type or more in-depth research on this topic. today it is something that should be given a relevant position in medical studies. After the analysis of the results of the examinations and radiography requested, it is determined based on the blood and radiological results where normal values are shown, so the doctor orders the patient to be discharged from hospital with a prescription of drugs to continue the treatment and visits to the doctor on a monthly basis to carry out a routine control and detract from a possible reappearance of this condition. The adult patient with community-acquired pneumonia managed to regenerate his health status gradually and vertiginously. In the same way, it was determined that there were improvements in the symptomatological picture that worried him, managing to restore his ventilatory quantifications, lung inoculation, vital signs and circulatory gases that were disturbed as a result of the bacterial cause that generated it.